Study of reading habits 1984 - Kalmar - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Kalmar. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Kalmar. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference.
Läsvanestudien 1984 - Kalmar
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap